Hexavalent Chromium Exposure Induces Intestinal Barrier Damage via Activation of the NF-κB Signaling Pathway and NLRP3 Inflammasome in Ducks - Xing, Chenghong; Yang, Fan; Lin, Yiqun; Shan, Jiyi; Yi, Xin; Ali, Farah; Zhu, Yibo; Wang, Chang; Zhang, Caiying; Zhuang, Yu; Cao, Huabin; Hu, Guoliang (Frontiers in Immunology, 2022)
Hexavalent chromium [Cr(VI)] is a dangerous heavy metal which can impair the gastrointestinal system in various species; however, the processes behind Cr(VI)-induced intestinal barrier damage are unknown. Forty-eight healthy 1-day-old ducks were stochastically assigned to four groups and fed a basal ration containing various Cr(VI) dosages for 49 days. Results of the study suggested that Cr(VI) exposure could significantly increase the content of Cr(VI) in the jejunum, increase the level of diamine oxidase (DAO) in serum, affect the production performance, cause histological abnormalities (shortening of the intestinal villi, deepening of the crypt depth, reduction and fragmentation of microvilli) and significantly reduced the mRNA levels of intestinal barrier-related genes (ZO-1, occludin, claudin-1, and MUC2) and protein levels of ZO-1, occludin, cand laudin-1, resulting in intestinal barrier damage. Furthermore, Cr(VI) intake could increase the contents of hydrogen peroxide (H2O2) and malondialdehyde (MDA), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-18 (IL-18) but decrease the activities of total superoxide dismutase (T-SOD), catalase (CAT), and glutathione reductase (GR), as well as up-regulate the mRNA levels of TLR4, MyD88, NF-κB, TNFα, IL-6, NLRP3, caspase-1, ASC, IL-1β, and IL-18 and protein levels of TLR4, MyD88, NF-κB, NLRP3, caspase-1, ASC, IL-1β, and IL-18 in the jejunum. In conclusion, Cr(VI) could cause intestinal oxidative damage and inflammation in duck jejunum by activating the NF-κB signaling pathway and the NLRP3 inflammasome.